Brand Image of Pesantren, Product Differentiation, and Its Impact on Consumer Loyalty: The Mediating Role of Consumer Satisfaction at the Basmalah Store - Uly Izzatun Nafilah; Asep Maulana Rohimat; Khairul Imam (Proceeding of International Conference on Islamic Boarding School, 2025)
The purpose of this study was to determine the effect of brand image and product differentiation on consumer loyalty in Basmalah stores through consumer satisfaction. The sample used was 100 people. The data analysis method used was analysis with the PLS-SEM method. Hypothesis testing was carried out through bootstrap testing. The results of the t-test, brand image has a significant effect on consumer loyalty , brand image has a significant effect on consumer satisfaction, product differentiation does not have a significant effect on consumer loyalty but has a significant effect if through consumer satisfaction as a mediating variable, product differentiation has a significant effect on consumer satisfaction, consumer satisfaction has a significant effect on consumer loyalty. Basmalah shop is necessary Keep going strengthening brand image and differentiation products offered​ For strengthen loyalty consumers .